The effectivity of salt in dry heat sterilization - Belen, Ma. Cristina; Escalante, Aleli; Tan, Jocelyn (Adviser).
Concerned with the need to maintain asepsis during root canal treatment, the researchers were prompted to conduct this study. The repeated use of the same file reintroduces bacteria into to cleansed canal and periapical region. Thus several methods of sterilization were done. Glass bead sterilization, is in fact, the most common method. However, fro reasons that - glass beads clog canal, easily lost and must be replenished, are not manufactured locally and high cost; an alternative was explored - salt.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental instruments and apparatus -- Sterilization; Salt